Juricultural pluralism vis-à-vis treaty law : state practice and attitudes - Bunn-Livingstone, Sandra L. (Developments in international law, 2002)
This title discusses how divergent individual, state, and regional cultures impact the international legal system in the law and state practice vis-a-vis treaty interpretation and reservations.